THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND WORKPLACE BULLYING ON SERVICE QUALITY - Hind Naeem Hoshi; Huda Abdulhaleem Ibrahim; Mohammed Raoof Al-Musawi; Alaa Abdulsalam Mustafa (Scholar Express Journals, 2025)
To identify the impact of transformational leadership and workplace bullying on service quality in Iraqi universities.
Keywords: Transformational leadership; workplace bullying; service quality